Research on stress evolution and segmented control of roadways under mining-induced disturbance in different influence periods - Yuxu SHEN; Junqing GUO; Chengshuai WANG; Heng WANG (Meikuang Anquan)
In view of the problems of drastic influence of mining, complex stress environment and difficult to control the surrounding rock, we take 090211 return roadway of Wangling Coal Mine as the research object, and use theoretical analysis, numerical simulation and on-site monitoring as the research means to study the stress evolution law of the roadway under the different spatial and temporal positional relationship between the driving roadway and working face under the condition of facing mining and driving. The segmented dynamic joint support method for the roadway in different influencing periods of the whole process of facing mining and excavation is proposed, and on-site monitoring is carried out. The results show that, based on the relative position relationship between the mining face and the tunneling roadway, the stress evolution process of the roadway being mined towards can be divided into three typical stages, including stress stable stage, unstable stress stage, stress reduction stage. The stress stable stage, with the action range being more than 50 m ahead of the working face, the vertical stress distribution curve of the roadway is in a symmetrical double-peak shape, and the stress distribution range is 11.8 MPa to 13.5 MPa. The unstable stress growth stage, with the action range being from 50 m ahead of the working face to 100 m behind it. The double-peak curve of the vertical stress of the roadway changes from symmetrical to asymmetrical. The maximum support stress of the coal pillar on the working face side is 27.1 MPa, with a stress increase of up to 67.3% compared to the previous stage. The stress reduction stage, with the action range being more than 100 m behind the working face. The influence of mining on the roadway gradually weakens, and the peak stress gradually decreases; the area 50 meters ahead of the working face to 100 meters behind it during the period of advancing towards the mining face is the stop-mining zone; the combined support effectively controlled the deformation of the surrounding rock of the roadway compared with the original support, the segmented approach of the roof and floor as well as the two sides was reduced by 34% to 38%, providing a feasible approach for the control of the surrounding rock of the roadway under the conditions of mining preparation and excavation.